Energy storage - Les Duckers (The Central European Review of Economics and Management (CEREM), 2022)
Aim: The aim of this paper is to explore Energy Storage requirements and options to suit the needs of systems and transport fed from renewables. The variability of wind and solar sources in particular and the demand for transport energy are seen as key issues. Design / Research methods: The paper outlines the need for energy storage and compares the energy density and power density of a selection of storage options. Conclusions / findings: The results illustrate the difficulties of finding storage mechanisms to rival fossil fuels in both energy density and power density. Moreover finding the natural resources to provide sufficient storage will be a serious challenge even though the economic costs of storage systems are falling. Originality / value of the article: The article demonstrates the importance of energy storage to the successful development of renewable energy systems, and of the economic and physical characteristics that such energy storage schemes should have. Implications of the research: Energy storage as a topic should be given a high priority for research and development. Limitations of the research: This article is not comprehensive and a review of best practice internationally would be a valuable extension to this work.
Keywords: Q42; 330; Renewable energy; Energy Storage; Climate Change